Legal Review Of Implementation Endowments Authority Relating To The Under Hand Agreement Made By Waqif (Case Study In Kua Wonosalam, Demak) - Dewi Farhati; Akhmad Khisni (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2018)
Waqf is a legal act of Waqif to separate and or hand over part of their wealth to be exploited forever or for a specified period. Usefulness of waqf itself for purposes of worship or public welfare according to the Shari'a. The purpose of the endowment given to nadzir of Waqif is to utilize waqf property in accordance with its function. The method used is a method socio-juridical with descriptive analytical research specifications, while the data analysis method used is qualitative analysis. Based on the results of research and discussion can be concluded that the power of the waqf agreement under the hand can be executed as long as their witnesses from several parties. During the relevant parties agree to the provision of the giiving waqf endowments by Waqif to nadzir have a valid legal provisions. Legally positive endowments implementation should be done with a pledge made before the Endowment Agreement Official Pledge (PPAIW) with two witnesses and should be made in the form of an agreement of Pledge of Endowments pursuant to Article 17 of Act No. 41 of 2004 on waqf: 1. Endowments statement implemented by Waqif to nadzir before PPAIW to be implemented by two witness; 2. Endowments statement referred to in paragraph (1) shall be declared orally and / or in writing and set forth in the agreement of pledge endowments by PPAIW.Keywords: Waqf, Endowments Authority, Under Hand Agreement.